Key Challenges in Advancing an Ecosystem-Based Approach to Marine Spatial Planning Under Economic Growth Imperatives - Lombard, Amanda T.; Dorrington, Rosemary A.; Reed, Jodie Romay; Ortega-Cisneros, Kelly; Penry, Gwenith Susan; Pichegru, Lorien; Smit, Kaylee Pam; Vermeulen, Estee Ann; Witteveen, Minke; Sink, Kerry J.; McInnes, Alistair M.; Ginsburg, Tayla (Frontiers in Marine Science, 2019)
In 2016, South Africa became the first African country to draft Marine Spatial Planning (MSP) legislation. The underlying legal framework supports the achievement of ecological, social and economic objectives, but a national policy to grow the oceans economy provides a challenge for ecosystem-based approaches to MSP. During the 2018 International Marine Conservation Congress in Borneo, we convened a special session to discuss particular challenges that will likely apply to any developing country seeking to increase profits from existing, or proposed, marine activities. Here we present six inter-disciplinary research projects that support ecosystem-based approaches to MSP in South Africa, by addressing the following key challenges: (1) measuring ecosystem condition; (2) modelling impacts of climate change on food webs and fisheries; (3) managing fisheries with an ecosystem approach; (4) using dynamic ocean management to resolve conflicts between fisheries and threatened species; (5) managing conflicting objectives in a growing marine tourism industry; and (6) developing scenarios for alternative management strategies in complex marine social-ecological systems.